A mesoscopic model of mechanical erosion for the characterization of ablation behavior of C/C woven composites. (1st June 2023) - Yang, Jing; Li, Wei; Ge, Jingran; Li, Weijie; Li, Yongshan; Liu, Shuo; Liang, Jun
Highlights: 1 The paper proposes a mechanical erosion failure criterion of C/C woven composites. 2 The criterion from 2D plain woven structure is extended to 2.5D woven structure. 3 A ablation program including a mechanical erosion failure criterion is developed. 4 Effects of weaving structure features on ablation behavior are investigated. Abstract: Carbon/carbon (C/C) composites suffer from the thermochemical ablation and mechanical erosion in the thermal protection system. A mathematical model describing the reaction/diffusion problem for the thermochemical ablation of C/C composites is established and numerically solved on the basis of the finite volume method and piecewise linear interface calculation. Then, a mesoscopic model including a failure criterion for the simulation of mechanical erosion of C/C woven composites is proposed. In the mesoscopic model of mechanical erosion, the mechanical erosion mechanism of C/C woven composites on the microscale is analyzed, and the mechanical erosion criterion of C/C woven composites from 2D plain woven structure is extended to 2.5D woven structure. The ablation performances of woven structures under thermochemical ablation with and without mechanical erosion criterion are compared, and the effects of weaving structure features on the ablation performances of 2.5D woven structure under simulated mechanical erosion are investigated. It shows that the mesoscopic model of mechanical erosion can well characterize the ablation behavior of C/C woven composites with different weaving forms. Some suggestions are provided for the design of C/C woven composites in the thermal protection system.